2009
DOI: 10.1007/s12291-009-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral ingestion of different forms of silver on tissue content of some essential elements in chicks

Abstract: Silver is ingested in India in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Copper concentrations recorded by Benito et al [21] in the blood of wild birds from the vicinity of the Do ňana National Park in Spain located in the area of influence of metal ore mines ranged from 0.133-0.586 mg/L. The copper content in the blood of chickens observed by Sharma et al [12] was 0.2-1.1 µg/g w/w, while in the liver it was 1.8-3.0 µg/g w/w and clearly decreased with increasing silver concentration, confirming the antagonistic effect of both elements. The concentration of copper in the blood serum of laying hens ranged from 3.4-5.3 µmol/L, depending on the housing system [22].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Copper concentrations recorded by Benito et al [21] in the blood of wild birds from the vicinity of the Do ňana National Park in Spain located in the area of influence of metal ore mines ranged from 0.133-0.586 mg/L. The copper content in the blood of chickens observed by Sharma et al [12] was 0.2-1.1 µg/g w/w, while in the liver it was 1.8-3.0 µg/g w/w and clearly decreased with increasing silver concentration, confirming the antagonistic effect of both elements. The concentration of copper in the blood serum of laying hens ranged from 3.4-5.3 µmol/L, depending on the housing system [22].…”
Section: Discussionmentioning
confidence: 93%
“…Sharma et al [12] analyzed the effect of ingesting various forms of silver with food on the content of selected chemical elements in chickens' tissues. The silver content in blood was 0.05-1.2 µg/g w/w, while that in liver ranged from 0.19 to 1.9 µg/g, depending on the form of silver taken in.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Sharma et al [16] investigating the effects of oral ingestion of different forms of silver on the content of essential elements in chick tissues showed a marked rise in the silver content in the liver, kidneys, spleen as well as in the blood of chickens fed nanosilver-supplemented feed, irrespective of the form of silver supplied. In their research on rats, Kim et al [8], observed the accumulation of this metal in all the studied tissues, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Although there has been no published study on silver residues in poultry meat and organs, some studies have investigated the accumulation of silver ions in various animal organ tissues. Sharma, et al [22] showed that feeding nano-silver compounds to chickens can accumulate in their tissues. In that study, silver was found in the liver, kidneys, spleen, and blood of chickens that were fed silver-contained supplements.…”
Section: Discussionmentioning
confidence: 99%